Review of Nitride-Based Multifunctional PVD-Deposited Coatings - Ardila-Tellez, Luis-Carlos; Orozco-Hernandez, Giovany; Estupiñan-Mongui, Fredy; Moreno-Téllez, Carlos-Mauricio; Olaya-Florez, Jhon-Jairo (Revista Científica, 2023)
The success of a functional coating is intrinsically linked to the improvement of its surface properties, as it is the surface that will be in direct contact with the environment and mechanical stresses when the material is used in severe wear, fatigue, or corrosion applications. It has been shown, for example, by increasing mechanical properties, that factors such as surface hardness increase the durability of the coating/substrate system. Consequently, current research on the design and development of multifunctional coatings for surface engineering within mechanical systems must address surface treatment and modification techniques. This article is a bibliographic review of coatings with industrial applications regarding transition metal nitrides deposited with physical vapor deposition (PVD) techniques such as sputtering and cathodic arc.